Pengembangan Modul Ajar Matematika Berbasis Literasi Terintegrasi Budaya Luwu di Sekolah Dasar - Mubarrozah, Mubarrozah; Ma’rufi, Ma’rufi; Patmaniar, Patmaniar (Universitas Cokroaminoto Palopo, 2025)
project aimed at developing and producing a teaching module that meets the criteria of validity, effectiveness, and efficiency. The research design adopts the ADDIE development model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 30 fifth-grade students in phase C. Data were collected through lesson implementation observation sheets, student and teacher response questionnaires, and student learning outcome tests. Data analysis involved pretest and posttest results using normality tests, homogeneity tests, and paired sample t-tests. The research results are as follows: (1) Expert validation from content experts, literacy experts, and cultural experts indicated that the module aligns with the learning objectives in terms of content, language, and literacy-based mathematical culture in elementary schools, achieving an average score of 91% categorized as very valid; (2) The developed module received student responses with an average of 89% and teacher responses of 88%, both interpreted as very practical; (3) Learning using the literacy-based mathematics teaching module integrated with Luwu culture was effective in improving student literacy, with an average N-Gain score of 0.62 (moderate category), lesson implementation reaching 88%, and student activity reaching 91.96%.